(3GdJOQjH h GdJOQjS GdEHOGYjs 260 (3WQjbI h fUjMI h JeQjf ddEHOGY aj GdJOQjH h GdJOQjSs - (3GdShjOGf, WGQb eMeOs ((3GdchjJs (3GdEHOGY GdacQjs, 2006)
(3cj Jchf eOQSkG h eOQHkG eHOYkG GbQC gPG GdcJGH agh jajO aj WQb GdJYdje h GdJOQjH GdMOjKI hjMJhj Ydi eLehYI cHjQI ef GdJeGQjf h GdegGQGJ GdYdejIs
(3GdJQHjI h GdWads
(3eJhGaQ efg GdWHYI GdQGHYI (B2010 (3HecJHI eUQ GdQFjSjIs
1 2 5 11 12 14
Keywords: (3GdJOQjHs; (3GdJOQjSs; (3GdJYdjes; (3WQb GdJOQjHs